STRATEGI PENGEMBANGAN OBJEK WISATA RUMAH LONTIOK OLEH DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KAMPAR - Sari Anggraini; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Tourism has an important role in the development of the country. In addition, tourism also has an influence on Regional Original Income (PAD) for Local Governments. Kampar Regency is one of the regencies in Riau Province which has a variety of tourism objects. One of the attractions in Kampar Regency is the Lontiok House tourist attraction. This Lontiok House tourism object has the potential to be developed. Therefore, a strategy is needed for the development of this Lontiok House tourism object so that it can develop and increase the interest of tourists to visit.The theory used is SWOT Analysis in the Strategic Management book by Sondang P. Siagian to determine the right strategy to overcome the problem. The research method uses qualitative methods with data collection carried out by interview, observation, and documentation with purposive sampling and accidental sampling techniques. The data analysis technique used was descriptive qualitative.The results of this study are the implementation of the Development Strategy of the Lontiok House Tourism Object by the Tourism and Culture Office of Kampar Regency but it is still not optimal in its implementation. Based on the results of the SWOT Analysis Strategy for the Development of Lontiok House Tourism Object that can be done is the synergy or cooperation of all components related to the development of tourism objects. Furthermore, there is a socialization of guidance and to the community on the importance of tourism awareness and allocating funds for the construction of facilities and infrastructure with the aim of increasing the number of tourist visits.Keywords: Lontiok House, Strategy, Tourism Object Development.